(untitled) (Baghdad Science Journal, 2025)
This work comprises the synthesis of new thioxanthone derivatives containing C-substituted thioxanthone. To obtain these derivatives, the o-mercapto benzoic acid was chosen as the starting material, o-mercapto benzoic acid with phenoxy acetic acid / thio phenoxy acetic acid gave 2-(oxy acetic acid) thioxanthone (1) and 2-(thio acetic acid) thioxanthone (2) respectively. Treatment of (1,2) with thionyl chloride gave 2-(oxy acetyl chloride) thioxanthone (3) and 2-(thio acetyl chloride) thioxanthone (4) respectively. Compounds (3,4) were treated with hydrazine hydrate (99%) to form the hydrazide (5,6) which is the desired Chiron, the hydrazide (5,6) was used to react with phenyl isothiocyanate / phenyl isocyanate to give thiosemicarbazide (7,8) / semicarbazide (9,10) derivatives respectively, which were used in the preparation of eight types of heterocyclic derivatives.